2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347321
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing near-falls from daily activities with wearable accelerometers and gyroscopes using Support Vector Machines

Abstract: Falls are the number one cause of injury in older adults. An individual's risk for falls depends on his or her frequency of imbalance episodes, and ability to recover balance following these events. However, there is little direct evidence on the frequency and circumstances of imbalance episodes (near falls) in older adults. Currently, there is rapid growth in the development of wearable fall monitoring systems based on inertial sensors. The utility of these systems would be enhanced by the ability to detect n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Apart from the different methods and predictors that were considered to be good in these studies [14][15][16] , all of our studies did find that the analysis of trunk acceleration may have the potential for evaluating the fall risk.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Apart from the different methods and predictors that were considered to be good in these studies [14][15][16] , all of our studies did find that the analysis of trunk acceleration may have the potential for evaluating the fall risk.…”
Section: Discussionmentioning
confidence: 98%
“…From the few studies that have used accelerometers to assess near-falls 15,16 , Weiss et al 14 were one of the first. Their results indicated that the maximum peak to peak difference in vertical jerk was the best single parameter to distinguish a near-fall from a non-fall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, Table 1 summarizes state-of-the-art solutions [11][12][13][14][15] declared to be able to recognize near falls. The table reports the architectures in terms of used acquisition equipment, fall indicators (i.e., the feature(s) to be monitored and classified) and chosen classification method.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the last two rows summarize the declared system performance (i.e., accuracy and efficiency) and the applicability of proposed systems to daily-life and/or ambulatory contexts, as well as their suitability in the context of real-time near falls detection and fall prevention. All the studies selected for the comparison analyze unexpected slippages, classifying them as near falls because all the perturbations analyzed in [11][12][13][14][15] led to balance recovery. Table 1 shows that the most used technologies in the loss of balance detection are motion capture systems (MCS) [12,13,15] and inertial measurement units (IMU) [11,14].…”
Section: Introductionmentioning
confidence: 99%